(untitled) (Journal of Enam Medical College, 2022)
Background: Hospital records reveal a gradual increase in the number of children with behavioral and cognitive problems. Maternal employment has also been rising steadily. However, little is known about the relationship between maternal employment and child’s behavioral and cognitive problems. Objective: To evaluate the child’s behavioral and cognitive problems and their relationship with maternal employment. Materials and Methods: This cross-sectional analytical study was conducted on 30 children aged 3−8 years, having cognitive and/or behavioral problems who fulfilled the enrollment criteria. Data were analyzed descriptively and Chi-square/Fisher’s exact tests were used wherever appropriate with significance set at p<0.05. Results: Children’s mean age was 5.5±2.0 years (M:F 1.3:1). Of all children, 73.3% were family’s 1st child, 83.3% belonged to nuclear family. Among parents 43% spent quality time with children. Among mothers 40% were service holders and others were housewives. All working mothers were employed before 3rd year of their children. Among working mothers 84% worked 8 hours per day. Externalizing and internalizing behavior problems, non-satisfactory school performance and non-disciplined activities were found higher among working mothers’ children compared to housewife mothers’ children (50.0% vs 38.9%; 16.7% vs 11.1%; 91.7% vs 88.9%; 50.0% vs 44.4%, respectively). In this study >1 behavior problems and delayed cognition were found higher among housewife mothers’ children (33.3% vs. 38.9%; 41.7% vs. 66.7%). In both groups, 83.3% children were not involved in extracurricular activities. Overall, Risk Ratios did not predict any risk of having behavioral problems with mothers’ employment (all p values >0.05). Conclusion: This study demonstrated no significant effect of maternal employment on developing child’s behavioral and cognitive problems. To generalize the findings, large-scale study is recommended. J Enam Med Col 2020; 10(3): 143-152